Cis- and trans-[SnR2] configurational isomers in diorganotin(IV) complexes containing mono or bidentate N-donor ligands - Momeni, Badri Z.; Kheirandish, Sadegh; Aghamohammadi, Niloofar; Noroozi, Vahid; Notash, Behrouz; Rominger, Frank (Polyhedron, 2013)
The reaction of diorganotin(IV) complexes SnR2Cl2 (R=Et, Ph) with the bidentate pyridyl ligand of 4,4′-di-tert-butyl-2,2′-bipyridine (bu2bpy) or phendione (phendione=1,10-phenanthroline-5,6-dione) resulted in the formation of the hexa-coordinated 1:1 adducts of [SnR2Cl2(NN] {R=Et, NN=bu2bpy (1); R=Et, NN=phendione (2); R=Ph, NN=bu2bpy (3)}. On the other hand, the reaction of SnPh2Cl2 with the corresponding monodentate ligand of 4-tert-butylpyridine (bupy) affords the 1:2 adduct of [SnPh2Cl2(bupy)2] (4). The solid state X-ray determination of complex [SnEt2Cl2(bu2bpy)] (1) revealed that the complex 1 contains the hexa- coordinated tin(IV) atom in an octahedral geometry with the trans-[SnEt2] configuration while the X-ray crystal structure determination of complex [SnPh2Cl2(bu2bpy)] (3) reveals that the tin atom is hexa-coordinated in a distorted octahedral geometry with an unusual feature of the cis-[SnPh2] configuration. On the other hand, two carbon, two chlorine and two nitrogen atoms from two pyridyl ligands form an octahedral geometry around tin(IV) atom with trans-C2, trans-N2 and trans-Cl2 configurations in [SnMe2Cl2(bupy)2] (5). The resulting products have been fully characterized by elemental analysis, multinuclear NMR (1H, 13C, 119Sn) and 2D NMR (HH- COSY, 1H-13C HMQC) spectroscopy.
Im Titel ist die Zahl "2" tiefgestellt
Gesehen am 01.06.2021